Photoionizational Plasmas. I. Theory - Salzmann, David; Takabe, Hideaki; Wang, Feilu; Zhao, Gang (The Astrophysical journal, 2011)
In this paper, an attempt is made to define the subject of photoionizational plasmas through rigorous mathematical formalism. The central results of this paper are the following. (1) A set of recursive equations is introduced for the computation of the charge state distributions in photoionizational plasmas. (2) Quantitative validity limits are given for both the collisional and the photoionizational domains. (3) A parameter that determines the charge state distribution in the photoionizational regime is introduced. (4) We provide detailed discussion about the most important components of the emission spectrum in the different equilibrium domains of the emitting plasma. Some of these components have not been reported so far as included in the analysis of such plasmas.